The unlawful combatant: humanitarian law's other - Salama, Hussein (AUC Knowledge Fountain, 2014)
The war on terror triggered a debate over the treatment of members of Al Qaeda captured by US forces. The central point of the paper is that this debate is merely the most recent iteration of a dialectic constitutive of international humanitarian law. Non-state combatants in warfare have always been the object of conflicting desires. The history of international humanitarian law could be seen as the history of different attempts to engage (by excluding or including) with an other, outside the combatant/civilian distinction. The Paper focuses on two contrasting approaches to engaging with this other, namely, the inclusive approach of the 1974-1977 Diplomatic Conferences in Geneva that lead to the promulgation of Additional Protocols I and II and the exclusionary experience with the war on terror.